DATA PROTECTION LAWS IN INDONESIA ANALYZING LEGAL IMPLICATIONS AND CASE STUDIES IN THE DIGITAL AGE - Dyani Rizkifitria; Zahra Annisa; Rizqyta Permata Khoerunissa; Avriel Silvio Delano Singal; Bardo Joshua (Problematika Hukum, 2020)
Navigating the data deluge of the digital age demands a nuanced approach to personal data protection. This research delves into this critical issue through a multifaceted lens, utilizing case studies and analysis of Indonesian data protection regulations. By examining real-life scenarios, we reveal the tangible challenges individuals and organizations face in managing personal data effectively. Our in-depth exploration of existing regulations provides a critical assessment of their strengths and limitations, paving the way for informed recommendations for future improvements. This contribution transcends mere theoretical analysis, offering a practical understanding of the complexities and intricacies of data protection law in Indonesia's dynamic digital landscape. By bridging the gap between theory and practice, this research empowers individuals, organizations, and policymakers to navigate the evolving landscape of personal data protection with greater clarity and confidence.Keywords: Personal Data Protection, Digital age, Legal Aspects.